Harmonising dawn raids in a global village: the ECN+ directive and negotiating legal certainty within fragmented european administrative procedure - Riina Autio (Market and Competition Law Review)
Administrative procedure remains largely unharmonized in the European Union. One area where the divergent national procedures are particularly visible are unannounced inspections or ‘dawn raids’. They are carried out by national competition authorities to enforce both national competition laws and the corresponding EU provisions, notably Articles 101 and 102 of the Treaty on the Functioning of the European Union. Provisions that are similar or even identical are thus being enforced under different procedural rules within the Union. Minimum harmonisation of competition law enforcement is underway with Directive 2019/1 or “ECN+”, as it became known in the early stages of the work towards the actual Directive. This article looks at different views to harmonisation and uneven enforcement and public statements from six EU Member States about the national amendments to implement Directive 2019/1. Dawn raids are always a balancing act between the public interest in uncovering competition infringements and fundamental and human rights, such as the right of defence. This article argues fragmentation poses a threat to legal certainty and does so in an area that routinely overlaps with fundamental and human rights. What is more, the ECN+ Directive may not level the playing field as intended. The current harmonisation efforts may, instead, carry a risk of merely shifting the existing imbalance to other areas of enforcement.